Real-life pilot study on the impact of the telemedicine platform EasyMICI–MaMICI® on quality of life and quality of care in patients with inflammatory bowel disease. (4th May 2021) - Bonnaud, Guillaume; Haennig, Audrey; Altwegg, Romain; Caron, Bénédicte; Boivineau, Lucile; Zallot, Camille; Gilleta de Saint-Joseph, Cyrielle; Moreau, Jacques; Gonzalez, Florent; Reynaud, Didier; Faure, Patrick; Aygalenq, Philippe; et al.
Abstract: Background: Telemedicine has shown promising results in the follow up of patients with inflammatory bowel disease. This study compared quality of life and disease activity in patients with inflammatory bowel disease monitored using a telemedicine platform versus standard care. Methods: In this prospective multicenter study, patients with active inflammatory bowel disease were randomized to EasyMICI–MaMICI ® telemedicine platform or standard care. The main objective was to assess the efficacy of the software platform, as measured by quality of life and quality of care. Secondary outcomes were changes in the use of healthcare resources, and patient satisfaction in the MaMICI group. Results: Fifty-four patients were enrolled (November 2017–June 2018); 59.3% had Crohn's disease and 40.7% ulcerative colitis. Forty-two patients received biologics at inclusion. After 12 months, a significant improvement in quality of life was observed with MaMICI versus standard care, with mean (standard deviation) changes from baseline of 14.8 (11.8) vs 6.3 (9.7) in the SIBDQ scores and 18.5 (18.7) vs 2.4 (8.3) in the EuroQol 5 D-3L questionnaire scores (both p ≤ .02). Disease activity was similar in both treatment groups. Use of MaMICI slightly reduced healthcare utilization versus controls (mean gastroenterologist consultations 2.2 vs 4.1; p = .1308). Overall satisfaction with MaMICI was high (mean score 7/10), and 46.2% of remaining patients in the MaMICI group continued to use the platform until 12 months. Conclusion: Significant improvement in quality of life and overall satisfaction with this telemedicine platform, indicates that further evaluation of EasyMICI–MaMICI in larger numbers of patients with inflammatory bowel disease is warranted.